1971
DOI: 10.1039/c29710000206
|View full text |Cite
|
Sign up to set email alerts
|

151Eu Mössbauer spectroscopic studies of “after effects” of the electron capture decay of151Gd

Abstract: Mossbauer spectroscopy has been used to observe the production of an 'anomalous' charge state, U ~E U ~+ , following the electron capture decay of 151GdS+ incorporated in Erz(Cz04)3, 10H20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1972
1972
1988
1988

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…A more detailed study of the Eu+ 2 formation in various rare earth trichloride-type host lattices is in progress and may elucidate this point. Similarly, the results of GLENTWORTH et al [12], who have observed formation of Eu+ 2 following the electron capture in a source of 161 Gd in Er 2 (C 2 0 4 ) 3 · 10H 2 0, and the absence of a line characteristic for Eu +a in our emission spectrum of 161 Sm in Sm 2 (C 2 0 4 ) 3 · 10H 2 0 suggest further experiments with other rare earth oxalates as host matrices.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A more detailed study of the Eu+ 2 formation in various rare earth trichloride-type host lattices is in progress and may elucidate this point. Similarly, the results of GLENTWORTH et al [12], who have observed formation of Eu+ 2 following the electron capture in a source of 161 Gd in Er 2 (C 2 0 4 ) 3 · 10H 2 0, and the absence of a line characteristic for Eu +a in our emission spectrum of 161 Sm in Sm 2 (C 2 0 4 ) 3 · 10H 2 0 suggest further experiments with other rare earth oxalates as host matrices.…”
Section: Discussionsupporting
confidence: 91%
“…However, an emission line attributed to Dy^ has been observed in the Mössbauer spectra of the 25.6 keV y-rays of lel Dy emitted after the ß~ decay of lel [10] to be either + 4 or predominantly + 3, depending on the annealing history of the sources. GLENTWORTH et al [11,12] studied the consequences of the ß~ decay of 161 Sm and the electron capture decay of 151 Gd, both populating the 21.6 keV Mössbauer level of 161 Eu. In a number of chelates of trivalent Sm and Gd they observed only the formation of Eu 4 " 3 [11], but the emission spectrum of a source of Er 2 (C 2 0 4 ) 3 · 10H 2 0 doped with 1B1 Gd was found to consist of two lines attributable to Eu+ 3 and Eu+ 2 with an intensity ratio of about 2:1.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the lifetime made by different authors are contradictory ranging from Modifications of the mechanism of Varley were later proposed [12 to 141. They involve the separation of the vacancy and interstitial atom at distances ensuring the stability of the Frenkel pair [ l a to 141, the possibility of formation of intermediate long-lived excited atomic configurations [ 13,141, and the replacement of the multiple ionization of an atom by single ionization of the neighbour atoms [ 12 to 141. However, there is a t present no convincing evidence for the realization of the Varley's mechanism or its modifications in alkali halide crystals.…”
Section: Introductionmentioning
confidence: 99%